One perfect summer - Novak, Brenda (Mira/Harlequin Enterprises, Limited, 2020)
"When Serenity Alston swabbed her cheek for 23andMe, she joked about uncovering some dark ancestral scandal. The last thing she expected was to discover two half sisters she didn't know existed. Suddenly, everything about her loving family is drawn into question. And meeting these newfound sisters might be the only way to get answers. The women decide to dig into the mystery together at Serenity's family cabin in Lake Tahoe. With Reagan navigating romantic politics at work and Lorelei staring down the collapse of her marriage, all three women are converging at a crossroads in their lives. Before the summer is over, they'll have to confront the past and determine how to move forward when everything they previously thought to be true was a lie. But any future is easier to face with family by your side."--Jacket flap.